Penerapan Metode REBA dan EFD dalam Perancangan Stasiun Kerja Ergonomis pada Proses Pencetakan Produk Tahu - Setyowati, Rinda; Jazuli, Jazuli; Setyaningrum, Ratih (Applied Industrial Engineering Journal, 2017)
The design of an ergonomic working system in the company of either manufacturing or service requires ergonomic methods in its application to help people adjust the work system with psychological and physiological factors, the goal is to avoid illness or accidents due to work and can increase comfort and work productivity. SME Know Sendang is one of the small-scale manufacturing companies engaged in the production of tofu products that experienced problems in the production process associated with high rates of work-related pain, especially spinal complaints experienced by employees on the production floor. The study started by measuring the level of potential work-related illness using the Neat Entire Body Assesment (REBA) method and the result of 3 high-risk action actions of 94% of potential workers could experience back pain due to traditional and non-ergonomic work positions especially on the process move the know to the printout. Work station improvements are designed using the Ergonomic Function Deployment (EFD) method to obtain ergonomic and ergonomic seating designs using anthropometric measurements of human working positions. The anthropometry calculation results show that the height of the ergonomic seating height is 105 cm, the length of the printed table is 1500 cm, the height of the printed table is 53 cm using the high anthropometric dimension of the knee and the height of the 65 cm valve using the height of the sitting elbow. The calculation validation was performed by calculating the final REBA value and obtained the value of action 1 with the low potency level and the potential backbone pain decreased to 20%.